Mehanske lastnosti prepletenih polimernih mrež - Anžlovar, Alojz (Kovine zlitine tehnologije, 1995)
The influence of the concentration of functional groups in polyurethane (pu) and polymethacrylate (pm) prepolymers as well as the influence of their mass ratio and average molecular weight on mechanical properties were investigated.
Keywords: polimeri; polimerne mreže; mehanske lastnosti